Empirical linkage between sustainable HRM and organisational flexibility: a SEM-based approach. (2018) - Vihari, Nitin Simha; Rao, M.K.; Jada, Umaamaheswararao
Sustainability has been regarded as a panacea for organisational flexibility from the past few years of management research, but there remains considerable research gap in terms of the empirical linkage between the latent constructs of sustainable HRM and organisational flexibility. The purpose of this paper is to explore whether the employee perceptions of sustainable HRM practices affects the organisational flexibility via three intervening variables such as employee voice behaviour, organisational learning culture and employee satisfaction. The authors find a positive association between the sustainable HRM practices and organisational flexibility. The results also suggest that the three intervening variables act as partial mediators corresponding to the direct linkage. This present study adds value because of the nascent stage of the sustainable HRM construct and less number of empirical studies that have examined the linkage between sustainability and flexibility, not only in the Indian context but also in the advanced economies.